MODIFICATION AND BIOLOGICAL ACTIVITY OF IMINE DERIVATIVE OF AMOXICILLIN - Sadiq S. Sadiq; Balsam Mohamed; Atyaf Qusay Kadhim; Abbas K. Abbas (European Science Publishing, 2024)
In this study, we report a novel imine-amoxicillin synthesis (A-C) by reacts amoxicillin with different aldehydes such as 2-hydroxybenzaldehyde, 4-methoxybenzaldehyde, and 4-butoxybenzaldehyde. The derivatives (A-C) were characterized by spectroscopic technique, such as FT‐IR and 1H-NMR spectroscopy. All the synthesized derivatives (A-C) were evaluated in vitro against different microorganisms such as Bacillus subtilis, Streptococcus pneumonia, E. coli, and Bacillus subtilis by zone inhibition method. The findings demonstrated that certain derivatives exhibit superior antibacterial properties in comparison to the efficacy of the original drug.
Keywords: Imine, Amoxicillin, Schiff base, Bacteria.